Rising waters, falling well-being: The effects of the 2013 East German flood on subjective well-being - Sachintha Fernando; Katharina Kolb; Christoph Wunder (Deutsches Institut für Wirtschaftsforschung (DIW), German Socio-Economic Panel (SOEP), 2025)
This paper employs a panel event study design to examine the causal effects of the 2013 flood disaster in East Germany on subjective well-being. We merge geo-spatial flood data with longitudinal data from the German Socio-Economic Panel (SOEP) to identify individuals in affected municipalities. Our results show that those affected by the flood report a significant life satisfaction drop of 0.17 points on an 11-point scale, which is equivalent to a 2.5% fall from pre-flood levels, in the year after the flood. The effect is more severe in peripheral areas than in central areas, and for low-income individuals than for high-income individuals. However, the effect dissipates by 2015. Additionally, we observe a notable initial decrease in health satisfaction, followed by recovery, while financial satisfaction was largely unaffected.
Keywords: I31; Q51; Q54; 330; natural disasters; flood; quality of life; life satisfaction; health satisfaction; financial satisfaction